2014
DOI: 10.1103/physrevlett.112.202503
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Origin of Nearly Degenerate Doublet Bands inAg106

Abstract: The lifetimes of the excited levels for the two nearly degenerate bands of 106 Ag have been measured using the Doppler-shift attenuation method. The deduced BðE2Þ and BðM1Þ rates in the two bands are found to be similar, except around the band crossing spin, while their moments of inertia are quite different. This is a novel observation for a nearly degenerate doublet band.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The evidence of the chiral doublet bands was first observed in 2001 [2]. So far, around 40 candidates of chiral doublet bands have been reported in A ∼ 80 [3,4], 100 [5][6][7][8][9][10], 130 [2,[11][12][13][14][15][16] and 190 [17,18] mass regions experimentally, see [19][20][21] for reviews. Theoretically, the chiral doublet bands are studied by the particle rotor model (PRM) [1,[22][23][24][25], the titled axis cranking (TAC) model [1,[26][27][28][29], the TAC plus random phase approximation [30], the collective Hamiltonian [31,32], and the interacting boson-fermion-fermion model (IBFFM) [33][34][35].…”
mentioning
confidence: 99%
“…The evidence of the chiral doublet bands was first observed in 2001 [2]. So far, around 40 candidates of chiral doublet bands have been reported in A ∼ 80 [3,4], 100 [5][6][7][8][9][10], 130 [2,[11][12][13][14][15][16] and 190 [17,18] mass regions experimentally, see [19][20][21] for reviews. Theoretically, the chiral doublet bands are studied by the particle rotor model (PRM) [1,[22][23][24][25], the titled axis cranking (TAC) model [1,[26][27][28][29], the TAC plus random phase approximation [30], the collective Hamiltonian [31,32], and the interacting boson-fermion-fermion model (IBFFM) [33][34][35].…”
mentioning
confidence: 99%
“…• The high-spin states of 106 Ag were populated through the 96 Zr( 14 N, 4n) reaction using a 68 MeV [161]. Two bands close in energy were pointed out.…”
Section: Discussionmentioning
confidence: 97%
“…40, the lifetimes of the excited levels for the lowest two nearly degenerate bands of 106 Ag are also measured using the Doppler-shift attenuation method. 41 The authors argued that similar transition rates but different moments of inertia observed in the doublet bands of 106 Ag may contain a novel observation for a nearly degenerate doublet band. 41…”
Section: /2mentioning
confidence: 97%
“…37 In A ∼ 100 mass region, the lifetime measurements have been performed for 103,104 Rh, 38 102 Rh 39 and 106 Ag. 40,41 Although the chiral partner bands have energies close to each other, it is rare to observe a crossing between them. Therefore, crossing of candidate chiral bands is important as a test of the onset of static chirality.…”
Section: Historical Reviewmentioning
confidence: 98%
See 1 more Smart Citation